Acute-on-Chronic Liver Failure in Pregnant Patients with Chronic Hepatitis B: A Retrospective Observational Case Series Study - Shiwei Wang; Haofeng Xiong; Changling Luo; Hong Zhao; Ying Fan; Ting Zhang; Lili Wang; Qi Wang; Wen Xie (Gastroenterology Research and Practice)
Background and Aims. Acute-on-chronic liver failure (ACLF) is common in patients with end-stage liver disease and chronic hepatitis B (CHB) or hepatitis B virus- (HBV-) related cirrhosis. To date, no uniform definition and management strategy are available for ACLF. Although a considerable number of studies on ACLF has been published, there are few reports on ACLF in pregnant women with CHB. This study retrospectively reviewed five patients who were diagnosed with ACLF during pregnancy in the past 10 years. We aimed at investigating their clinical characteristics, treatment, biochemical test results, and maternal and fetal outcomes. Results. Asthenia, anorexia, and jaundice were the main initial clinical manifestations in these patients during the second or third trimester of pregnancy. All patients received antiviral therapy. None of the pregnant women died after treatment. Patient #4 was treated with an artificial liver support system, and patients #2 and #5 underwent transfusion therapy. The acute insult in all patients was HBV DNA reactivation. Except for patient #3, who chose an actively induced vaginal delivery because of intrauterine fetal demise, the remaining four patients underwent a preterm delivery via a cesarean section. The four neonates were alive, although all were small for gestational age. Conclusion. Asthenia, anorexia, and jaundice during mid-late pregnancy should be immediately investigated. Before and during the pregnancy, hepatologists or obstetricians should actively screen pregnant women with CHB for HBV DNA status and alanine aminotransferase levels. Reactivation of HBV replication in pregnant women with CHB may lead to ACLF, especially in multiparous women. Once ACLF is diagnosed, antiviral therapy should be considered as soon as possible to protect maternal and fetal health.